Effects of blended learning in public physical education course on exercise attitude, motor skills, and physical fitness among non-sports major undergraduates in Luoyang, China - Wang, Chen (2024)
The study sets out to assess the effect of blended learning on exercise attitude, motor skills, and physical fitness among non-sports major undergraduates in public physical education courses. Employing a Cluster Randomized Control Trial and a pretest-posttest true experimental design, the research meticulously examines these effects. The evaluation utilizes three key instruments: The Basketball Skills Assessment for motor skills, the National Student Physical Health Standard for physical fitness, and the Exercise Attitude Scale by Zhang & Mao (2010) to gauge exercise attitude. Dividing 320 students into experimental (blended learning) and control (traditional learning) groups, the study implements a blended learning approach using a Massive Open Online Course (MOOC) as the experimental treatment, while the control group receives conventional teaching methods. Statistical analysis, employing two-way repeated measures ANOVA, reveals significant differences (p < .01) in interactions (time* group) across all measured variables, including exercise attitude, motor skills, and physical fitness. Furthermore, the study demonstrates that, for the simple main effect of time within the group, significant differences were observed between blended and traditional learning models across most variables in exercise attitude, motor skills, and physical fitness, except for the 50-meter run (p = .025) and BMI (p = .822) in the traditional learning model (p < .01). Similarly, significant differences were noted for the simple main effect of the group within the time for most variables in exercise attitude, motor skills, and physical fitness (p < .01) during the post-test. However, notable differences emerged during the posttest in exercise attitudes (behavior cognition (p = .037), subjective standard (p = .027)) and physical fitness (BMI (p = .036), sit and reach (p = .034), and 50- meter run (p = .049)). Conversely, no significant differences were observed in exercise attitude (behavior control (p = .268)) and physical fitness (1000/800- meter run (p = .083)). The study underscores the transformative potential of blended learning in enhancing students' exercise attitudes, motor skills, and physical fitness, suggesting its superiority over traditional teaching methods in physical education. However, recognizing the study's limitations, such as its confined scope to a single academic level and semester duration, the research advocates for replication across diverse educational levels and longitudinal formats. Furthermore, it proposes integrating qualitative or mixed methods to offer deeper insights for educators regarding the effective implementation of blended learning strategies. These recommendations are poised to bolster the generalizability of the findings and foster informed long-term educational planning.